Compound-Specific Radiocarbon Analysis of Atmospheric Methane: A New Preconcentration and Purification Setup. Issue 5 (October 2019) - Espic, C; Liechti, M; Battaglia, M; Paul, D; Röckmann, T; Szidat, S
ABSTRACT: Methane contributes substantially to global warming as the second most important anthropogenic greenhouse gas. Radiocarbon ( 14 C) measurements of atmospheric methane can be used as a source apportionment tool, as they allow distinction between thermogenic and biogenic methane sources. However, these measurements remain scarce due to labor-intensive methods required. A new setup for the preparation of atmospheric methane samples for radiocarbon analysis is presented. The system combines a methane preconcentration line with a preparative gas chromatography technique to isolate pure methane samples for a compound-specific radiocarbon analysis. In order to minimize sample preparation time, we designed a simplified preconcentration line for the extraction of methane from 50 L atmospheric air, which corresponds to 50 µg C as required for a reliable 14 C analysis of methane-derived CO2 gas measurement with accelerator mass spectrometry (AMS). The system guarantees a quantitative extraction of methane from atmospheric air samples for 14 C analysis, with a good repeatability and a low processing blank. The setup was originally designed for the measurement of samples with low methane concentrations, but it can also be adapted to apportion sources from environmental compartments with high methane levels such as freshwaters or wetlands.